Chapter Uses and Written Practices in Aljamiado Manuscripts - Castilla, Nuria de (Studies in Manuscript Cultures, 2019)
Crossing disciplinary and regional boundaries, this book takes a comparative perspective on standardisation tendencies in Arabic-based writing systems across three continents. 12 distinct manuscript traditions are presented in situations where different cultures, languages and scripts interact, yielding a wide range of case studies. A wealth of new data gives insight into the factors underlying uniformity and variation in manuscript cultures.